2003
DOI: 10.1103/physrevc.68.034606
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and incoherent giant dipole resonanceγ-ray emission induced by heavy ion collisions: Study of the40Ca+48

Abstract: Coherent and incoherent dipolar ␥-ray emission is studied in a fully dynamical approach by means of the constrained molecular dynamics model. The study is focused on the system 40 Caϩ 48 Ca for which recently experimental data have been collected at 25 MeV/nucleon. The approach allows us to explain the experimental results in a self-consistent way without using statistical or hybrid models. Moreover, calculations performed at higher energy show interesting correlations between the fragment formation process, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In these first two stages of development, the model has been used to investigate processes induced by heavy-ion collisions at Fermi energies with particular reference to the excitation of the fluctuating and coherent dipolar modes, cluster production, dynamical fission processes and incomplete fusion processes. Examples of these studies are [357][358][359][360][361][362][363]).…”
Section: Pauli-blockingmentioning
confidence: 99%
“…In these first two stages of development, the model has been used to investigate processes induced by heavy-ion collisions at Fermi energies with particular reference to the excitation of the fluctuating and coherent dipolar modes, cluster production, dynamical fission processes and incomplete fusion processes. Examples of these studies are [357][358][359][360][361][362][363]).…”
Section: Pauli-blockingmentioning
confidence: 99%
“…It has been shown that CoMD (as well as other codes, e.g. BNV, BUU, TDHF) predicts the development of a collective behavior during the interaction of the projectile with the target in a peripheral or semi-peripheral collision [59,60]. A certain time is necessary for a neck to develop between the projectile and the target after their contact.…”
Section: Confrontation Of Model Calculations With the Datamentioning
confidence: 99%
“…[58][59][60] and ref. therein) that the process has a collective character resembling a large amplitude dipole motion.…”
Section: Introductionmentioning
confidence: 99%